2017
DOI: 10.4252/wjsc.v9.i10.179
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde dehydrogenase activity helps identify a subpopulation of murine adipose-derived stem cells with enhanced adipogenic and osteogenic differentiation potential

Abstract: AIMTo identify and characterize functionally distinct subpopulation of adipose-derived stem cells (ADSCs).METHODSADSCs cultured from mouse subcutaneous adipose tissue were sorted fluorescence-activated cell sorter based on aldehyde dehydrogenase (ALDH) activity, a widely used stem cell marker. Differentiation potentials were analyzed by utilizing immunocytofluorescece and its quantitative analysis.RESULTSApproximately 15% of bulk ADSCs showed high ALDH activity in flow cytometric analysis. Although significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The present study contains the results confirming the expression of intracellular markers vimentin, desmin, αSMA, and the activity of aldehyde dehydrogenase (ALDH). The level of ALDH is currently used as a selection marker of the stem cells due to its relation to self-renewal and differentiation abilities [ 54 , 55 ]. The phenotypic profile was confirmed by flow cytometry and PCR methods on the mRNA level.…”
Section: Discussionmentioning
confidence: 99%
“…The present study contains the results confirming the expression of intracellular markers vimentin, desmin, αSMA, and the activity of aldehyde dehydrogenase (ALDH). The level of ALDH is currently used as a selection marker of the stem cells due to its relation to self-renewal and differentiation abilities [ 54 , 55 ]. The phenotypic profile was confirmed by flow cytometry and PCR methods on the mRNA level.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Harumichi et al [ 72 ] reported that although significant differences in proliferation capacity were not seen, the adipogenic and osteogenic differentiation capacities were higher in aldehyde dehydrogenase (ALDH)-high subpopulations than in ALDH-low subpopulations. All these studies revealed that osteogenic potential is related to different subpopulations.…”
Section: Advances In Related Basic Researchmentioning
confidence: 99%
“…Although ALDH br cells with stem cell properties have been detected in various normal tissues, including the bone marrow [ 14 , 23 ], umbilical cord blood [ 24 , 25 ], mammary glands [ 26 , 27 ], heart [ 28 ], and adipose tissue [ 29 ], little is known about lung-resident ALDH br cells. A study showed that isolated murine airway basal and submucosal gland duct ALDH br cells exhibited stem cell properties in normal/healthy lungs [ 30 ].…”
Section: Discussionmentioning
confidence: 99%